Application of Discovery Learning Model in Practical Learning to Improve Students' Communication and Collaboration Skills - Firdiawan Ekaputra (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this study was to examine the effectiveness of the application of the discovery learning model in practicum learning to improve student communication and collaboration skills. The samples used in this study were students who attended inorganic chemistry practicum lectures in the 2022/2023 academic year. This research is a quasi-experimental type of research with class R-002 as the experimental class and R-004 as the control class. Data on communication and collaboration skills were obtained using questionnaire techniques which were then processed with the manova test. The results obtained show that the application of the discovery learning model in practicum learning is effective for improving student communication and collaboration skills.